Review of Clean Water Supply System Development's Feasibility in Indonesia's Samosir Regency - Sitohang, Oloan; Munthe, Kornel; Manurung, Edison Hatoguan; Naibaho, Pio Ranap Tua; Wardiningsih, Sitti (Universitas Negeri Yogyakarta, 2023)
Around 15,352 families (42.66 percent) in Samosir Regency still have access to clean water, which is still a rather low percentage compared to the remaining 20,638 families (57.34 percent) who do not. The local government is concerned with this situation in order to create the BUMD PDAM Samosir Regency. This research was done to see if it would be possible to start a local water firm in Samosir Regency. In order to determine whether there is a potential water source that is adequate, sustainable, and manageable economically and profitably in the context of public services, as well as whether the establishment of PDAM Samosir Regency is worth reviewing, interviews and questionnaires were distributed to the community, SPAM owners, and State Civil Servants. In addition to socioeconomic factors, there are financial factors, market factors, legal factors, managerial factors, organizational factors, and technical factors. Legal, social and economic, technical, and notably from economic considerations with IRR = 72.32> I = 12 percent / year, PP = 3.34, and BCR = 6.27, BUMD PDAM Samosir Regency is viable to be founded